'Fat mass and obesity associated' gene (FTO): No significant association of variant rs9939609 with weight loss in a lifestyle intervention and lipid metabolism markers in German obese children and adolescents - Müller Timo D; Hinney Anke; Scherag André; Nguyen Thuy T; Schreiner Felix; Schäfer Helmut; Hebebrand Johannes; Roth Christian L; Reinehr Thomas (BMC, 2008)
Abstract Background We have previously identified strong association of six single nucleotide polymorphisms (SNPs) in FTO (fat mass and obesity associated gene) to early onset extreme obesity within the first genome wide association study (GWA) for this phenotype. The aim of this study was to investigate whether the obesity risk allele of one of these SNPs (rs9939609) is associated with weight loss in a lifestyle intervention program. Additionally, we tested for association of rs9939609 alleles with fasting blood parameters indicative of glucose and lipid metabolism. Methods We initially analysed rs9939609 in a case-control study comprising 519 German overweight and obese children and adolescents and 178 normal weight adults. In 207 of the obese individuals who took part in the outpatient obesity intervention program 'Obeldicks' we further analysed whether carrier status of the obesity risk A-allele of rs9939609 has a differential influence on weight loss after the intervention program. Additionally, we investigated in 480 of the overweight and obese patients whether rs9939609 is associated with fasting blood levels of glucose, triglycerides and HDL and LDL-cholesterol. Genotyping was performed using allele specific polymerase chain reaction (ARMS-PCR). For the association study (case-control approach), the Cochran-Armitage trend test was applied. Blood parameters were analysed using commercially available test kits and the log10-transformed blood parameters and changes in BMI-standard deviation scores (BMI-SDS) were analysed by linear regression with sex and age as covariates under an additive mode of inheritance with the rs9939609 A-allele as risk allele. Results We confirmed the association of the risk A-allele of rs9939609 with overweight and early onset obesity (one sided p = 0.036). However, we observed no association of rs9939609 alleles with weight loss or fasting levels of blood glucose, triglycerides and cholesterol. Conclusion We confirmed the rs9939609 A-allele as a risk factor for early onset obesity whereas its impact on weight loss or on serum levels of glucose, triglycerides and cholesterol could not be detected in our samples. Trial Registration This study is registered at clinicaltrials.gov (NCT00435734).